1996
DOI: 10.1002/(sici)1096-9896(199603)178:3<352::aid-path474>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Anti-GBM Glomerulonephritis Induced in Rats by Immunization With Synthetic Peptides Based on Six Α Chains of Human Type Iv Collagen

Abstract: The anti‐glomerular basement membrane (GBM)‐nephritis‐inducing activity of six synthetic peptides having an amino acid sequence consisting of the six α chains of human type IV collagen was examined by injecting the peptides into rats. The peptides consisted of 27 amino acid residues from the non‐collagenous domain (NC1) of the α1 to α6 chains and were non‐consensus sequences sandwiched between two consensus sequences near the carboxyl terminus. Each peptide was coupled to keyhole limpet haemocyanin and injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…6D). This nding corresponded to the literature reporting that the α3subunit of Col (IV) is distributed in the basement membrane of renal tubules in rats [19]. IHC demonstrated the reveal of α3(IV)NC1 in the affected renal interstitial tissues of Group 2 rats with anti-GBM antibody production and in ltration of CD11c + macrophages around the sites but not in Groups 1 and 2 rats without anti-GBM antibody production (Fig.…”
Section: Production Of Anti-gbm Antibody In Exacerbated Aav Model Ratssupporting
confidence: 90%
“…6D). This nding corresponded to the literature reporting that the α3subunit of Col (IV) is distributed in the basement membrane of renal tubules in rats [19]. IHC demonstrated the reveal of α3(IV)NC1 in the affected renal interstitial tissues of Group 2 rats with anti-GBM antibody production and in ltration of CD11c + macrophages around the sites but not in Groups 1 and 2 rats without anti-GBM antibody production (Fig.…”
Section: Production Of Anti-gbm Antibody In Exacerbated Aav Model Ratssupporting
confidence: 90%
“…The antigen is derived from solubilized GBM [13], or a purified fraction containing a(IV)NC1 domains [14]. Synthetic a3(IV)NC1 or a4(IV)NC1 peptide sequences [15] or recombinant a3(IV)NC1 or a4(IV)NC1 proteins [16][17][18] have also be used. Studies on actively induced anti-GBM nephritis have revealed the target antigen of nephritis to be a3(IV)NC1 and a4(IV)NC1.…”
mentioning
confidence: 99%
“…However, only three clones of nephritogenic monoclonal antibodies have been characterized [15,21], and this number is too small to know the nature and function of nephritogenic autoantibodies. In 1995 we reported a new monoclonal-antibody-producing method called the rat lymph node method [23].…”
mentioning
confidence: 99%
“…Since then, improved active type models induced in rats by a single injection of an emulsion of soluble nephritogenic antigen from GBM and adjuvant have become widely applied. [3][4][5][6][7][8] Passive types of experimental anti-GBM nephritis can also be induced by injections of homologous polyclonal 9 or monoclonal 10,11 antibodies to the GBM or type IV collagen.…”
Section: Introductionmentioning
confidence: 99%
“…31 In addition, injection of a synthetic peptide that contains part of the human 4(IV)NC1 sequence can induce experimental anti-GBM nephritis in rats. 11 We developed a novel method of generating rat monoclonal antibodies that uses the enlarged medial iliac lymph nodes (as a source of B cells) from rats injected with emulsified antigen into their hind footpads. 33 The frequency of positive hybridomas producing antibodies to the immunogen is about ten times higher than that obtained by the conventional method using mouse or rat splenic lymphocytes as a source of B cells.…”
Section: Introductionmentioning
confidence: 99%